The 12-month prevalence of psychotic experiences and their association with clinical outcomes in Hong Kong: an epidemiological and a 2-year follow up studies - Chan, Sherry Kit Wa; Lee, Kaspar Kit Wai; Chan, Veronica Hei Yan; Pang, Herbert H.; Wong, Corine Sau Man; Hui, Christy Lai Ming; Chang, Wing Chung; Lee, Edwin Ho Ming; Chan, Wai Chi; Cheung, Eric Fuk Chi; Chiu, Helen Fung Kum; Chiang, Tin Po; et al. (Psychological medicine, 2021)
The relationship between the subtypes of psychotic experiences (PEs) and common mental health symptoms remains unclear. The current study aims to establish the 12-month prevalence of PEs in a representative sample of community-dwelling Chinese population in Hong Kong and explore the relationship of types of PEs and common mental health symptoms. This is a population-based two-phase household survey of Chinese population in Hong Kong aged 16-75 (N = 5719) conducted between 2010 and 2013 and a 2-year follow-up study of PEs positive subjects (N = 152). PEs were measured with Psychosis Screening Questionnaire (PSQ) and subjects who endorsed any item on the PSQ without a clinical diagnosis of psychotic disorder were considered as PE-positive. Types of PEs were characterized using a number of PEs (single v. multiple) and latent class analysis. All PE-positive subjects were assessed with common mental health symptoms and suicidal ideations at baseline and 2-year follow-up. PE status was also assessed at 2-year follow-up. The 12-month prevalence of PEs in Hong Kong was 2.7% with 21.1% had multiple PEs. Three latent classes of PEs were identified: hallucination, paranoia and mixed. Multiple PEs and hallucination latent class of PEs were associated with higher levels of common mental health symptoms. PE persistent rate at 2-year follow-up was 15.1%. Multiple PEs was associated with poorer mental health at 2-year follow-up. Results highlighted the transient and heterogeneous nature of PEs, and that multiple PEs and hallucination subtype of PEs may be specific indices of poorer common mental health.